PERILAKU KONSUMEN DALAM MENGGUNAKAN E-COMMERCE PADA MASA PANDEMI COVID-19 DI TINJAU DARI PERSPEKTIF EKONOMI ISLAM - ., Bayu (Sekolah Tinggi Ekonomi Dan Bisnis Islam Darussalam, 2020)
This study aims to find out how concumers behavior in the people in Blambangan Umpu Village, Way Kanan District in using e-commerce transactions during the Covid-19 pandemic, viewed from an Islamic economic perspective. This type of research uses a qualitative descriptive approach with primary and secondary data types taken through interviews, documentation and literature studies. The results of this study concluded that consumer behavior in the community in Blambangan Umpu Village Way Kanan District was active in using e-commerce transaction. People are more likely to use e-commerce transactions to meet primary or dharurriyat needs aimed at obtaining blessings and benefits. The frequency of e-commerce usage in the Blambangan Umpu District continued to increase significantly during the Covid-19 pandemic.